(3OjhGf eMeO GdOeTbj (B((3OjhGf hYX(B)s - (3UdGM GdOjf CHhGdUaG eMeO GdOeTbj,J (B821 (3g` s
(3ChdgG (B:s
(3ENhGfj CPcQhG Gdjhe GdehYhO, hYQVg Ydi GdfGQ PGJ GdhbhO s
(3BNQgG (B:s
(3jG ef Edjg YGjI GdeQJLi CQMe def TcQc ef OGHg LGQjI bO fXeJ gPg Yf YLR age djS JQVi Hg s
(3gfGc Tc aj GSe eDda GdeNWhWIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B301s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B201 s
(3eUOQ GbJfGA GdCUd (B:s
(3CdeGfjG (B(38) s
Keywords: (3GdCOHs